Towards solving baby dumping issue in Malaysia by using the alternative way: baby hatch - Termizi, Mazbah; Abdul Majid, Azizah; Tagaranao, Mariam Saidona; Mohd Safian, Yasmin Hanani (2014)
Baby dumping issue has become a serious phenomenon in Malaysia. The fact that newborn babies being dump to die at the most inappropriate places such as toilet or junkyard is such a heinous crime. Despite various steps taken by governments and societies, the statistic of baby dumping is escalating in Malaysia. This should not be happening in our country to uphold our image as a Muslim nation. This research, not only will discuss the literature review with regards to the issue of baby dumping in Malaysia, but also shedding some overview of the alternative way of curbing this problem which is known as baby hatch. Opinions from the NGO (such as OrphanCare Foundation) and judiciary are referred to, in order to find the best possible method to overcome this baby dumping issue in Malaysia. This is as an alternative to the legal procedure which falls under Penal Code and other related Acts. The comparisons are needed in order to seek the best possible way of the solution of the baby dumping in Malaysia and to find the perception of the public on the alternative way of the solution of baby dumping, i.e. baby hatch.